Development of an ablation tool for oil palm - and K. Sudhakarbabu, M.V. Prasad, T. Vidhan Singh (Journal of Plantation Crops, 2018)
Ablation is the process of removing unopened inflorescence from oil palm plantations during juvenile period (1 to 3 years). The ablation tool developed consists of a long handle of 2.54 cm diameter GI pipe having 152.4 cm length. At one end of this pipe, a “U” shaped welded holder has been made of 1 inch flat with 5±1 mm thickness and 19 cm length, which has a width of 2 cm at the welding point, and gradually widened to 5.2 to 5.7 cm at the outer end. A sharp pointed nail having 6.5 cm length and 5 to 8 mm diameter was welded at the centre of the “U” holder. In the traditional method of removing the inflorescence, at least 2.4 leaves were cut to remove one inflorescence whereas, with the developed tool, the leaves are not damaged or removed. Farmers generally avoid removal of the inflorescence during 1 to 3 years thereby hampering the growth and yield in the forthcoming years. The efficiency of the ablation tool is 125 inflorescence per hour.